2013
DOI: 10.5223/pghn.2013.16.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality on Liver Function Test

Abstract: Children with abnormal liver function can often be seen in outpatient clinics or inpatients wards. Most of them have respiratory disease, or gastroenteritis by virus infection, accompanying fever. Occasionally, hepatitis by the viruses causing systemic infection may occur, and screening tests are required. In patients with jaundice, the tests for differential diagnosis and appropriate treatment are important. In the case of a child with hepatitis B virus infection vertically from a hepatitis B surface antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 15 publications
5
37
0
Order By: Relevance
“…Both total protein and albumin concentrations in blood plasma are considered as markers of the liver functioning, reflecting partly its nutritional status (Kang, 2013). In the present study, unaffected total plasma protein and increased plasma albumin level in pigs fed both experimental diets may indicate physiological liver and gallbladder functions.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Both total protein and albumin concentrations in blood plasma are considered as markers of the liver functioning, reflecting partly its nutritional status (Kang, 2013). In the present study, unaffected total plasma protein and increased plasma albumin level in pigs fed both experimental diets may indicate physiological liver and gallbladder functions.…”
Section: Resultsmentioning
confidence: 66%
“…The above may be confirmed by the fact that we showed significantly lower plasma activity of GGT in pigs fed diet with chicory root addition. Kang (2013) suggested that increased ALP activity with the significant increase in GGT activity must originate from the liver rather than metabolic activity of bones. Additionally, in human adolescents predominant ALP serum activity derives from bone origin ALP fraction as the effect of intense skeletal growth (Van Hoof et al, 1990;Kang, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from this study were supported the assumption that heavy elements released in feeds cooked in cooking pots made of Atmonia and Pepsi cans were the main reasons of high elevation of liver functioning enzymes of Wistar rats such as AST, ALT and ALP. Alkaline ) an enzyme also found in the liver, bile Soo Kang, 2013). High levels of these enzymes may cause liver damage or disease, a blocked bile Paul and Giboney, (2005) reported that some toxic heavy elements were able to cause significant increase in LDH amounts in liver.…”
Section: Serum Alp and Ldh Levels Were Measured By The Hitach 902mentioning
confidence: 99%
“…The results obtained from this study were supported the assumption that heavy elements released in feeds cooked in cooking pots made of Atmonia and Pepsi cans were the main reasons of high elevation of liver functioning enzymes of Wistar rats such as AST, ALT and ALP. Alkaline phosphatase (ALP) an enzyme also found in the liver, bile ducts, and bones (Ki-Soo Kang, 2013). High levels of these enzymes may cause liver damage or disease, a blocked bile duct, or bone disease.…”
Section: Cv% = 158% Se+ = 136mentioning
confidence: 99%